2020
DOI: 10.1155/2020/3594963
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Crossing Behavior and Violations of Electric Bikers at Signalized Intersections

Abstract: This paper focuses on investigating electric bikers’ (e-bikers) crossing behavior and violations based on survey data of 3,126 e-bikers collected at signalized intersections in Nantong, China. We first explore e-bikers’ characteristics of late crossing, incomplete crossing, and violating crossing behaviors by frequency analysis and duration distribution, and examine a few influential factors for e-bikers’ red-light running (RLR) behavior, including site type, crossing length and traffic signal countdown timers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Due to the low power output, the acceleration rate or deceleration rate, which also can be seen as the e-bike riders' stop-go decision, was the most critical factor affecting the speed of e-bike. With regard to the number of acceleration rate changes for e-bikers, consistent with the study proposed by Tang [31], the e-bikers who could know the remaining time of amber light from the countdown timer are more likely to accelerate to clear the intersection. e-bikers who decided not to change their initial acceleration rate (keep accelerating to pass the stop line) were found to have YLR violation with the probability of 271% higher than the riders who change their initial decision once time.…”
Section: Analysis Of the Number Of Acceleration Rate Changessupporting
confidence: 78%
See 3 more Smart Citations
“…Due to the low power output, the acceleration rate or deceleration rate, which also can be seen as the e-bike riders' stop-go decision, was the most critical factor affecting the speed of e-bike. With regard to the number of acceleration rate changes for e-bikers, consistent with the study proposed by Tang [31], the e-bikers who could know the remaining time of amber light from the countdown timer are more likely to accelerate to clear the intersection. e-bikers who decided not to change their initial acceleration rate (keep accelerating to pass the stop line) were found to have YLR violation with the probability of 271% higher than the riders who change their initial decision once time.…”
Section: Analysis Of the Number Of Acceleration Rate Changessupporting
confidence: 78%
“…In our study, the natural observation results showed that 63% of e-bikers had a YLR violation when they arrived at intersection facing signal change interval, which is slightly lower than the result proposed by Bharat [13] (the proportion of YLR violation was 68.6% in motorized two wheel). However, the proportion of YLR e-bikers is relatively higher than the result reported by Tang et al [31] (the proportion of the GR near-violation, also called YLR violation, was 32%). e difference between these two studies may be caused by the different data collection process, which is that we only collected the e-bike riders' crossing behaviour who faced the signal change interval, while in Tang's study the authors recorded all e-bike riders' crossing behaviours during peak hours.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Four types of factors have been identified in the literature that affect the probability of cyclists’ traffic violations, including sociodemographic (e.g., age and gender), psychological (e.g., attitude and subjective norms), riding condition (e.g., if they are carrying a passenger and using a phone), and ambient road environment (e.g., traffic volume and intersection types) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Despite that these studies provided valuable information for improving road safety, they cannot capture the interdependency between cyclists’ traffic violations and enforcement strategies (e.g., police patrol intensity and penalty severity for traffic violations).…”
Section: Introductionmentioning
confidence: 99%